"Need for Speed": Framework for Measuring Construction Project Pace – Case of Road Project. (14th July 2016) - Zidane, Youcef J-T.; Andersen, Bjørn; Johansen, Agnar; Ahmad, Saad
Abstract: The construction industry relies on time-to-delivery to gain competitive advantages and increase profit margins. The aim of this paper is to develop a framework for measuring construction project speed. This will be done by identifying a range of key performance indicators (KPIs). This identification of KPIs helps set a benchmark for measuring the speed of a construction project. In this paper, a conceptual framework is presented to reflect the idea behind the use of performance measurement in measuring the speed of construction projects, and then a performance measurement system tailored to a real case of a road construction project.